STUDIES OF THE APPLICATION OF COATINGS ON THE DRILL BLADE - Juraev Jurabek Malikovich; Yuldoshev Mirzobek Nurilloevich (Galaxy International Interdisciplinary Research Journal, 2021)
The article covers technological process of applying coatings by PVD-method and analysis of variations of deposition